Breve historia del teatro en la ciudad de Loja - Gonzaga Correa, Tania Elizabeth (2014)
The following research is about the brief history of The Theater in Loja. It has the purpose of showing a good historical compilation of the theater in Loja. Under this context, it was established, as a main goal, to contribute to the culture of Loja throughout a practical outline that talk about the changes of the theater thru history. In order to obtain what was explained before, it was necessary to summarize historical testimonies about the theater in Loja, to identify the most noticeable playwrights of this city and it was also consider important to recall the theatrical groups of Loja. Considering that history is the base of this research, it has an historical analysis, it has taken into account a bunch of memories of a selected group of eye witnesses of the facts that were history approximately since the last thirty years of the past decade. During the process of the development of this research, it was necessary to use the following methods: analytical, synthetic, deductive, inductive and chronological; these methods allowed to obtain the following results: a chronological chart about the changes of the history of the theater in Loja and a compilation of some works of literature, moreover some groups and theatrical companies of the city were recognized in the present research. In this way, it was determined that the historical development of the theater in Loja started approximately since 1970 and the national University of Loja was one of the institutions that encouraged the theater in Loja. Nowadays, the support of other entities such as The Private University of Loja and The Ecuadorian Cultural House are trying to re-start the theatrical culture in the city of Loja.